2007
DOI: 10.1016/j.jom.2006.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Outsourcing impact on manufacturing firms’ value: Evidence from Japan

Abstract: Previous studies on the effects of outsourcing have relied largely on anecdotal evidence, non-financial metrics or accountingbased measures that ignore intangible value. This study views outsourcing effects from its future revenue-generation potential, using market value. The relation between firms' market valuation and outsourcing decisions is investigated using a cross-sectional valuation approach. Results based on Japanese manufacturing industries data from 1994 to 2002 indicate that core business-related o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(86 citation statements)
references
References 63 publications
1
83
0
2
Order By: Relevance
“…In fact, human assets are specific when professional accountants require specialized knowledge of the specific characteristics of the firm so as to carry out a specific accounting function (Everaert et al, 2010). According to TCE, when asset specificity is low, and transactions are relatively frequent, transactions might be governed by outsourcing (Watjatrakul, 2005;Jiang et al, 2007;Chang et al, 2009). In other words, higher levels of asset specificity would lead to a lower amount of the core businesses being outsourced (Chang et al, 2009;Jiang et al, 2007).…”
Section: Asset Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, human assets are specific when professional accountants require specialized knowledge of the specific characteristics of the firm so as to carry out a specific accounting function (Everaert et al, 2010). According to TCE, when asset specificity is low, and transactions are relatively frequent, transactions might be governed by outsourcing (Watjatrakul, 2005;Jiang et al, 2007;Chang et al, 2009). In other words, higher levels of asset specificity would lead to a lower amount of the core businesses being outsourced (Chang et al, 2009;Jiang et al, 2007).…”
Section: Asset Specificitymentioning
confidence: 99%
“…According to TCE, when asset specificity is low, and transactions are relatively frequent, transactions might be governed by outsourcing (Watjatrakul, 2005;Jiang et al, 2007;Chang et al, 2009). In other words, higher levels of asset specificity would lead to a lower amount of the core businesses being outsourced (Chang et al, 2009;Jiang et al, 2007). However, human asset specificity is an important driver for the outsourcing in internal audit function (Spekle´ et al, 2007), and accounting services (Everaert et al, 2010).…”
Section: Asset Specificitymentioning
confidence: 99%
“…Indeed, human assets are specific when professional accountants entail specialized knowledge of the particular attribute of a business concern (Everaert et al, 2010) while to perform a special accounting function. In accordance with TCE, when transactions are somewhat recurrent and asset specificity is low, such transactions are most likely to be governed by outsourcing (Chang et al, 2009;Jiang et al, 2007;Watjatrakul, 2005). TCE argues that once the accounting tasks entail high intensity of asset specificity, the search for external accountant will be extensive (Nicholson et al, 2006) and contractual negotiations are more argumentative (Espino-Rodríguez et al, 2008).…”
Section: Asset Specificitymentioning
confidence: 90%
“…Some authors identified negative relationships between outsourcing and indicators like market share when outsourcing reaches a level over a certain optimum [28]. Other studies showed that outsourcing really reduces operational costs [29]. Fuchs and Kirchain showed how wages, yields, downtimes and other parameters are dependent on the location of a factory and demonstrated that with real case data from the optoelectronics industry [30].…”
Section: Importance Of the Production Depth In Literaturementioning
confidence: 99%